Role of aggressive locoregional surgery in treatment strategies for ipsilateral supraclavicular lymph node metastasis of breast cancer: a real-world cohort study - Feng, Kexin; Xing, Zeyu; Dai, Qichen; Cheng, Han; Wang, Xiang (Frontiers in Molecular Biosciences, 2023)
Background: Breast cancer patients with synchronous ipsilateral supraclavicular lymph node metastases (ISLNM) have unfavorable prognoses. The role of supraclavicular lymph node dissection (SLND) as a surgical intervention in the treatment of this condition remains controversial. In this study, we aimed to evaluate the prognostic factors associated with breast cancer with ISLNM and to assess the potential impact of aggressive locoregional surgical management on patient outcomes.We conducted a retrospective analysis of 250 breast cancer patients with ISLNM who were treated with curative intent at our institution between 2000 and 2020. The cohort was stratified into groups based on the extent of axillary surgery. The first group, comprising 185 patients, underwent level I/II axillary dissection. The second group, consisting of 65 patients, underwent aggressive locoregional surgery, including levels I/II/III (infraclavicular) dissection in 37 patients and levels I/II/III + SLND in 28 patients. Our study evaluated overall survival (OS) and disease-free survival (DFS) as primary endpoints, and locoregional recurrence-free survival (LRRFS) and distant metastasis-free survival (DMFS) as secondary endpoints.Results: The median follow-up time among all patients was 5.92 years (1.05-15.36 years). The 5year OS rate was 71.89%, while the DFS rate, LRRFS rate, and DMFS rates were 59.25%, 66.38%, and 64.98%, respectively. A significant difference in OS, DFS, LRRFS, and DMFS was observed between the second group and the first group (P < 0.01). No beneficial impact on recurrence, metastasis, or survival outcomes was observed in the levels I/II/III + SLND group compared to the This is a provisional file, not the final typeset article levels I/II/III dissection group. Multivariate logistic regression analysis revealed that levels I/II/III ± SLND surgery and T stage were associated with OS (P = 0.006 and P = 0.026), while levels I/II/III ± SLND surgery, ER+/HER2-, and histologic grade were associated with DFS (P = 0.032, P = 0.001, P = 0.032).Conclusions: Breast cancer with ISLNM may be considered a locoregional disease, requiring a combination of systemic and local therapies. Aggressive locoregional surgery has been shown to positively impact recurrence, metastasis, and survival outcomes. This approach may provide improved management of the ISLNM for breast cancer patients.